Cremation in an Islamic Perspective: Cremation Practices in Jakarta - Aisyah Khoniwardah; Ari Hasbya Rahmatika; Rindi Rahmawati F.T.N; Zaidatul Hidayah N.A (al-Afkar, Journal For Islamic Studies, 2026)
This research argues that cremation is not only problematic from a religious aspect, but also from an economic aspect. The limited number of burial plots and the high monthly cost of renting land are the main factors in thr increase in cremation rates in Indonesia. Some of it is also due to traditions and customs.This research uses qualitative methods with a theoretical approach viewed from legal and economic aspects. Various scientific articles and books have been analyzed to understand how cost considerations and land limitations influence people in carrying out cremation, as well as how Islamic law views cremation.